1 Soiled airway tracheal intubation and the effectiveness of decontamination (SATIATED) by paramedics: a randomised controlled manikin study. (26th April 2019) - Pilbery, R; Teare, MD
Abstract : Background: In more than 20% of out-of-hospital cardiac arrests, the patient's airway is soiled. 1 2 If the airway cannot be cleared, the patient will die. A new method of clearing the airway, suction assisted laryngoscopy and airway decontamination (SALAD) has been developed, but it's not known whether this method can assist paramedics to intubate. 3 This study aims to determine whether paramedics can intubate a simulated soiled airway more often on their first attempt, using SALAD. Method: A modified airway manikin, with the oesophagus connected to a reservoir of 'vomit' and bilge pump, was used to simulate a soiled airway. The intervention was a brief SALAD training session with a demonstration and opportunity to practice. Participants were randomly allocated into two groups: AAB who made two pre-training intubation attempts and one post-training attempt, and ABB, who made one pre-training and two post-training attempts, to adjust for improvement due to repetition. Results: 164 paramedics took part in the study. First-pass intubation success with and without SALAD was 90.2% and 53.7% respectively, a significant difference of 36.6% (95%CI 24%–49.1%, p<0.001). The mean successful intubation time for each attempt and patient group (AAB and ABB) was as follows: 61.8 (95%CI 55.8–67.8) and 59.4 (95%CI 53.6–65.1) s on the first attempt, 50.8 (95%CI 45.7–55.9) and 51.5 (95%CI 48.6–54.4) s on the second attempt and 53.5 (95%CI 50.4–56.6) and 46.6 (95%CI 44.0–49.1) s on the third attempt. Conclusion: In this study, paramedics were able to intubate a simulated soiled airway on their first attempt, significantly more often when using the SALAD technique. Reference: Voss S, Rhys M, Coates D, Greenwood R, Nolan JP, Thomas M, et al . How do paramedics manage the airway during out of hospital cardiac arrest? Resuscitation 2014 Dec;85(12):1662–6. Simons RW, Rea TD, Becker LJ, Eisenberg MS. The incidence and significance of emesis associated with out-of-hospital cardiac arrest. Resuscitation 2007 Sep;74(3):427–31. DuCanto J, Serrano KD, Thompson RJ. Novel Airway Training Tool that Simulates Vomiting: Suction-Assisted Laryngoscopy Assisted Decontamination (SALAD) System. West J Emerg Med 2017 Jan;18(1):117–20. Conflict of interest: R. Pilbery is a research paramedic at Yorkshire Ambulance Service NHS Trust. MD. Teare has no conflicts of interest. Funding: This research was funded by a College of Paramedics small research grant.